The influence of HIV infection on the age dependence of squamous cell carcinoma of the skin in South Africa - Diffey, B L; Norval, M; Albers, P N; Wright, C Y (South African medical journal, 2017)
Cancer incidence typically increases with age, but it is not known whether ethnic characteristics influence the age dependence of squamous cell carcinoma of the skin (SCC). (i) To determine the age dependence of SCC in the black African, coloured and white population groups of South Africa (SA); and (ii) to show whether any differences in the rate of change of age dependence could be influenced by diversity in behaviour and lifestyle, especially with regard to the prevalence of HIV infection, rather than by a fundamental variation in cancer biology between the populations. Linear regression analysis was applied to the logarithm of the age-specific incidence rates for SCC v. the logarithm of age between 35 and 74 years. The slopes of the regression (age exponent) were compared for each subset of gender, population group and year of diagnosis (between 2000 and 2010). The most notable feature was the low value of the age exponent in both male and female black African compared with the white and coloured populations. This finding could be explained in part by the difference in the prevalence of HIV infection in the black African population group compared with the white and coloured population groups. The prevalence of HIV infection in black Africans in SA tends to decrease the apparent age component in SCC compared with the white and coloured population groups. Other factors relating to lifestyle and behaviour that differ between the population groups are also likely to influence the age component in SCC.